PERSEPSI KEADILAN WAJIB PAJAK ATAS KENAIKAN NILAI JUAL OBJEK PAJAK : (STUDI KASUS PADA WAJIB PAJAK PBB P2 DI KAB. BULELENG) - Putu Cornelia; A.A. Ngurah Candra Pratama; Kadek Kartika Gita Wahyuni; I Nyoman Putra Yasa (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
This study aims to determine the correlation of the increase in land and building tax in rural and urban areas in Buleleng Regency, Perception of Taxpayer Justice towards Taxpayer Compliance with the implementation of Regional Regulation Number 14 year 2018 concerning Amendments to Regional Regulation Number 5 of 2013. The draft used in this study is a qualitative approachmethod with interactive data analysis techniques, namely researchers conduct data analysis directly in the field by conducting interviews in data collection. Respondents in this study were people in Buleleng Regency. Based on interviews obtained from respondents, it was revealed that taxpayers objected to the significant increase in the Sales Value of Tax Objects (NJOP) and the increase in NJOP affected taxpayer compliance. The perception expressed in this study can be used as advice for the government and tax authorities to consider aspects of justice in the implementation of the taxation process in Buleleng Regency.